MONITORING KASUS TUBERCULOSIS BERBASIS GOOGLE EARTH - Bahtera Bin David Purba (Jurnal Penelitian Kesmasy, 2019)
Tuberculosis is one of the world's health problems including in Indonesia. In 2017 the number of new tuberculosis cases in the Deli Tua Health Center area reached 143 cases with a success rate of 76% and MDR TB reaching 15%. This decrease in cases was caused by improper drug uptake and MDR TB medication dosage errors and non-compliance with taking medication. To overcome the problem, Google Earth mapping and calendar documentation were applied. The results of the implementation show that there is a difference which means the completeness of treatment before and after the intervention with RR = 2.21; 95% CI: 1.32-3.69, cure rate for tuberculosis cases with RR = 1.87; 95% CI: 1.17-2.99, the dropout rate for treatment with RR = 1.77; 95% CI: 1.07-2.95, and mortality rate. Google Earth-based tuberculosis case intervention increased treatment completeness by 18.3%, improved tuberculosis case recovery by 15.9%, decreased tuberculosis case dropout rates by 12.5% and decreased tuberculosis case fatality rates by 4.4%. It was concluded that the Google Earth-based tuberculosis case monitoring system was effectively implemented in the work area of the Public health center in Deli Tua. It is recommended to use of Google Earth-based tuberculosis monitoring system.